Excessive Cellular S-nitrosothiol Impairs Endocytosis of Auxin Efflux Transporter PIN2 - Ni, Min; Zhang, Lei; Shi, Ya-Fei; Wang, Chao; Lu, Yiran; Pan, Jianwei; Liu, Jian-Zhong (Frontiers in Plant Science, 2017)
GSNOR1 (S-nitrosoglutathione reductase) is the key enzyme that regulates cellular levels of S-nitrosylation across kingdoms. We have previously reported that loss of GSNOR1 resulted in impaired auxin signaling and compromised auxin transport in Arabidopsis, leading to the auxin-related morphological phenotypes. However, the molecular mechanism underpinning the compromised auxin transport in gsnor1-3 mutant is still unknown. Endocytosis of plasma-membrane (PM)-localized efflux PIN proteins play critical roles in auxin transport. Therefore, we investigate whether loss of GSNOR1 function has any effects on the endocytosis of PIN-FORMED (PIN) proteins. It was found that the endocytosis of either the endogenous PIN2 or the transgenically expressed GFP-PIN2 was compromised in the root cells of gsnor1-3 seedlings relative to Col-0. The internalization of PM-associated PIN2 or GFP-PIN2 into Brefeldin A (BFA) bodies was significantly reduced in gsnor1-3 upon BFA treatment in a manner independent of de novo protein synthesis. In addition, the exogenously applied GSNO not only compromised the endocytosis of GFP-PIN2 but also inhibited the root elongation in a concentration-dependent manner. Together, our results indicate that, besides the reduced PIN2 level, one or more compromised components in the endocytosis pathway could account for the reduced endocytosis of PIN2 in gsnor1-3.